1995
DOI: 10.1021/j100017a019
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Generation of the Unstable BrCNO Molecule and Its Stable Dibromofuroxan Dimer. He I Photoelectron, Photoionization Mass Spectroscopy, Mid-Infrared, and ab Initio Studies

Abstract: The haloformonitrile oxide BrCNO has been generated for the first time in the gas phase from the dibromoformaldoxime precursor by pyrolysis or by chemical reaction with HgO(s) or NHsfg). Trapping this gaseous species leads to the ring dimer dibromofuroxan. The BrCNO and (BrCNOh species are characterized in the gas phase by Hel photoelectron spectroscopy, Hel and HLa photoionization mass spectroscopy, and infrared spectroscopy. The geometry of BrCNO obtained from ab initio calculations at the HF, MP" ( = 2-4), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 8 publications
(10 reference statements)
10
64
0
Order By: Relevance
“…Notice that the planar geometries of conformers 9, 12, and 13, correspond to transition states as their Hessian posses one imaginary frequency. In general terms, halogen substitution does not appear to affect the length of the nominally double CϭN bond (deviations of only 0.001 Å were observed), a result comparable to that observed for Cl and Br substitution on formaldoxime 7 and ethylene. 20 However, chloro-or bromo-substitution affects slightly the C-O bond, being shortened by 0.008 Å.…”
Section: Calculated Structures and Stability Of Xhfaox Conformerssupporting
confidence: 70%
See 2 more Smart Citations
“…Notice that the planar geometries of conformers 9, 12, and 13, correspond to transition states as their Hessian posses one imaginary frequency. In general terms, halogen substitution does not appear to affect the length of the nominally double CϭN bond (deviations of only 0.001 Å were observed), a result comparable to that observed for Cl and Br substitution on formaldoxime 7 and ethylene. 20 However, chloro-or bromo-substitution affects slightly the C-O bond, being shortened by 0.008 Å.…”
Section: Calculated Structures and Stability Of Xhfaox Conformerssupporting
confidence: 70%
“…Thus, ClCNO and BrCNO are predicted to adopt a linear geometry at the B3LYP, MP3, MP4SDQ, QCISD, and CCSD levels and a bent geometry at the MP2, MP4SDTQ, QCISD(T), and CCSD(T) using the 6-31G** basis set. 7 More recent calculations 9 of the molecular parameters of chloro-and bromo-fulminates using large-scale ab initio methods, such as coupled-cluster method, CCSD(T), and basis sets of double-through quintuple-zeta quality revealed that both molecules adopt a bent geometry. Our calculations predicted a trans bent structure for ClCNO and BrCNO in their singlet 1 AЈ ground states.…”
Section: Calculated Structures and Relative Stabilities Of Cxno Isomersmentioning
confidence: 99%
See 1 more Smart Citation
“…The equilibrium structures of HCC-NCO isomers (1,2,3,4,5) and transition states (6,7,8,9,10,11,12) were calculated at the ab initio MP2(full)/6-311G(2d,2p) level and also using the density functional theory in the form of Becke's three-parameter exchange functional in combination with the Lee, Yang and Parr correlation functional, B3LYP/6-311G(2d,2p). Harmonic vibrational frequencies were then calculated at the minimum energy geometries to make sure they were real minima on the potential energy surface (zero imaginary frequency).…”
Section: Methodsmentioning
confidence: 99%
“…This concurs with experimental results; the gas-phase thermolyses of dichloro-and dibromofuroxan do not produce nitrile oxide monomers. 26,52,55 This also suggests that gas-phase thermal generation of the unknown FCNO species from the furoxan is unfeasible. On the other hand, our experiments (UPS and/or FTIR) have shown that gas-phase thermal cycloreversion of dimethyl-and dicyanofuroxan, at temperatures for both molecules in the relatively narrow range of 550-600 1C (10 À3 to 10 À1 Torr), rapidly and quantitatively leads to monomeric CH 3 CNO, 27 and NCCNO.…”
Section: Dimerisation To Furoxansmentioning
confidence: 99%